PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MOTIVASI KEWIRAUSAHAAN TERHADAP KETERAMPILAN BERWIRAUSAHA MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 JAKARTA - Doddy Astya Budy (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2017)
The study sains to investigate: the extent to which entrepreneurship education affects entrepreneurial motivation of students of economics education, and  the extent to which entrepreneurship education affects their entrepreneurial motivation skills. The study was a causal associative study employing the quantitative approach. The research variables were entrepreneurship education as the independent variable and entrepreneurial motivation and skills as the dependent variables. This was a population study involving respondents who were students of University 17 Agustus 1945 Jakarta with a total of 88 students. The data were collected through a questionnaire and documentation. They were analyzed by means of simple linear regression. The results of the study entrepreneurship education positively and significantly affects entrepreneurial skills significance. Keywords: Entrepreneurship Education, Entrepreneurial Motivation, Entrepreneurial Skills